Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s13202-017-0369-4
|View full text |Cite
|
Sign up to set email alerts
|

Using ultrasonic as a new approach for elimination of inorganic scales (NaCl): an experimental study

Abstract: Because inorganic scales reduce permeability near wellbores, they cause an additional pressure drop in this region (skin damage) and reduce production. NaCl precipitation, particularly in gas-producing wells, is one of the formation damage problems which impair the permeability. The use of backwashing water not only requires a large quantity of water, but is also inefficient. This study examined the effect of the ultrasonic waves in NaCl scale removal. Twenty core samples with different permeabilities were sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
3
5
0
Order By: Relevance
“…Results showed that while increasing the ultrasound frequency, only transducer 1-3 produced better cleaning effect as shown in Figure 5b, implying that higher frequency may have a minor impact on the deposited scales. Some of their findings were in agreement with the experimental results of Taheri-Shakib et al [27]. Taheri-Shakib et al [27] used ultrasound to treat NaCl scales and restore the near wellbore permeability damaged by the inorganic scales, while demonstrating the influence of core permeabilities.…”
Section: Effect Of Ultrasound On Formation Damage In Porous Mediasupporting
confidence: 76%
See 1 more Smart Citation
“…Results showed that while increasing the ultrasound frequency, only transducer 1-3 produced better cleaning effect as shown in Figure 5b, implying that higher frequency may have a minor impact on the deposited scales. Some of their findings were in agreement with the experimental results of Taheri-Shakib et al [27]. Taheri-Shakib et al [27] used ultrasound to treat NaCl scales and restore the near wellbore permeability damaged by the inorganic scales, while demonstrating the influence of core permeabilities.…”
Section: Effect Of Ultrasound On Formation Damage In Porous Mediasupporting
confidence: 76%
“…Some of their findings were in agreement with the experimental results of Taheri-Shakib et al [27]. Taheri-Shakib et al [27] used ultrasound to treat NaCl scales and restore the near wellbore permeability damaged by the inorganic scales, while demonstrating the influence of core permeabilities. Some core samples from Iranian reservoirs with permeability ranges of less than 20, 30-100, 100-700md, and higher than 1000md were used to carry out the experiments.…”
Section: Effect Of Ultrasound On Formation Damage In Porous Mediasupporting
confidence: 76%
“…Furthermore, combined water flooding and US treatment created wormholes in the KCl crystals which improved the scale withdrawal. Similar behavior of integrated water injection and US for the treatment of NaCl scales was reported by Taheri-Shakib et al [74] in a different study. They showed that the water flooding with US increased the permeability recovery as compared to water injection, with the enhancement reaching 51% in some cases.…”
Section: Recent Progress In the Utilization Of Us In Oil Technologiessupporting
confidence: 85%
“…There are several studies that have attempted to improve the permeability and pore structure of porous media which have been damaged, and hence, improve the oil recovery of the reservoir [71] , [72] , [73] , [74] , [75] , [76] , [77] . Some of these studies have focused on the removal of inorganic salts causing formation damage in the near wellbore region ( Fig.…”
Section: Recent Progress In the Utilization Of Us In Oil Technologiesmentioning
confidence: 99%
See 1 more Smart Citation